Sulcus vocalis: evidence for autosomal dominant inheritance - Martins, Regina Helena Garcia [UNESP]; Goncalves, T. M. [UNESP]; Neves, D. S. [UNESP]; Fracalossi, T. A. [UNESP]; Tavares, E. L. M. [UNESP]; Moretti-Ferreira, D. [UNESP] (Funpec-editora, 2011)
We found evidence of autosomal dominant hereditary transmission of sulcus vocalis. Four dysphonic patients from three generations of the same family were submitted to videolaryngoscopic examination (three patients) and to direct laryngoscopy ( one patient) to diagnose the hoarseness. Sulcus vocalis was diagnosed in all four patients. The finding of four affected individuals in three generations, with vertical transmission affecting man and women, is more consistent with autosomal dominant inheritance pattern; it is an etiological model that we propose for the sulcus vocalis in this pedigree.
Keywords: Autosomal dominant; Sulcus vocalis; Hoarseness; Videolaryngoscopy; Genetics; Laryngeal development